Glycemic status and effect on mortality: Multifactorial prevention programme for cardiovascular disease in Finnish primary care - Kuneinen, Susanna M.; Kautiainen, Hannu; Ekblad, Mikael O.; Korhonen, Päivi E. (Elsevier, 2026)
AIMS: To compare 13-year mortality rates in normoglycemic, prediabetic and diabetic subjects attending a community-based screening and intervention programme.
METHODS: Population survey identified 2569 cardiovascular disease (CVD) white risk subjects aged 45-70 years and without manifested CVD or diabetes. Oral glucose tolerance test was performed, and multifactorial intervention was provided. Effect of glycemic status on mortality was estimated in models adjusted for age, gender, education years, smoking, body mass index, mean arterial pressure, total cholesterol, and physical activity.
RESULTS: Of the subjects, 2055 (77 %) were normoglycemic, 380 (14 %) had prediabetes and 224 (9 %) diabetes. Compared to the normoglycemic group, the fully adjusted hazard ratios (HR) for all-cause mortality were 1.34 (95 % CI: 0.98-1.83) in the prediabetes group and 2.31 (95 % CI: 1.62-3.31) in the diabetes group. Standardized mortality rates were 0.63 (95 % CI: 0.54-0.73), 0.91 (95 % CI: 0.69-1.18), and 1.55 (95 % CI: 1.19-2.02) in the normoglycemic, prediabetes, and diabetes groups, respectively. The most common cause of death was cancer (42 % of all deaths), followed by CVD (28 %).
CONCLUSIONS/INTERPRETATION: Screen-detected diabetes carries a substantial risk of death even after primary care intervention. The pattern of excess mortality has shifted towards cancer deaths.